Neuropsychomotor development and genomic stability associated to folate and blood iron levels in preschool children - Maiara de Queiroz Fischer; Patrícia Molz; Liziane Hermes; Caroline dos Santos; Luana Beatriz Limberger; Diene da Silva Schlickmann; Jorge André Horta; Jane Dagmar Pollo Renner; Daniel Prá; Silvia Isabel Rech Franke
Abstract Objectives: to evaluate the neuropsychomotor development and the genomic stability associated to folate and blood iron levels in preschool children. Methods: a cross-sectional study in which evaluated the biochemical exams (complete hemogram, serum ferritin, iron and folate), neuropsychomotor development (Denver II Test) and genotoxicity (micronuclei cytome in buccal mucosa cells) of 55 children aging 36-59 months old. Student´s T test, Kruskal-Wallis and Pearson's or Spearman's correlation tests were applied with a significance level of p<0.05 for data analysis. Results: the prevalence of anemia was 1.8%. The Denver II test classified 32.7% of the children as normal and 67.3% were suspected of having a delay. The children suspected of having a delay presented a slight reduction on hemoglobin and hematocrit (p=0.05 and p=0.14), intermediate reduction on iron and folate (p=0.29 and p=0.23) and a notable reduction on ferritin (p=0.03). Folate and iron were significantly associated to the frequency of cells with DNA damages (p<0.05). The frequency of binucleated cells was positively associated to the Red Cell Distribution Width (RDW) (r=0.56; p=0.02) in children without a delay and negatively with folate (r=-0.334; p=0.047) in children with a delay. Conclusions: this study showed a low prevalence of anemia, but a high rate of children suspected of having a neuropsychomotor, possibly associated to low ferritin levels. Additionally, iron and folate were associated to DNA damage which may have contributed to the psychomotor development delay.